Atributos do terreno na diferenciação e no mapeamento digital de solos - Soares, Julio Cesar Wincher (2015)
Terrain attributes control many hydrological, geomorphological and pedological processes, these processes influence the solar radiation, rainfall, runoff, evapotranspiration, soil moisture and the distribution of vegetation. In this way, the terrain attributes were extracted from MDE's high resolution (0.5 m) and accuracy to explain the differentiation of the soils of northeast region in the Rio Grande do Sul State, Brazil; also, to assess the accuracy of an MDS generated and soil maps obtained by the traditional soil survey, using the Kappa index, the overall accuracy, the user accuracy and correctness of the producer. Four representative catenas soils were studied of the landscape of the northeast region in the Rio Grande do Sul State. Terrain attributes analyzed by multivariate techniques showed to be effective in the differentiation of the soil, especially elevation, slope, the moisture content of the soil and the LS factor. The accuracy of the MDS was classified as excellent. The attributes of slope upstream slope, moisture content of the soil, elevation, LS factor and plane curvature in the